As atividades de coordenação e a gestão do conhecimento nos projetos de edificações - Silva, Maria Vitória Marim Ferraz Pinto da (Universidade Federal de São Carlos, 2004)
This work presents a study about the coordination of building designs and knowledge management. In the coordination activities, the focus is on the coordination management, related to the planning and to the administration of design process, and on the technical coordination, regarding the integration and the design development, all of them being promoted through the coordination meetings, the compatibilization and the critical analysis. The building design coordination has as its attribution to reconcile and to integrate the knowledge of several specialties. The work introduces the application of the knowledge management into the building design and discusses the knowledge and competences needed for the coordination activities and development of the building design. The knowledge management is fundamental to reorganize the processes of generating, registering, diffusing and usage of the organizational knowledge. Moreover, the information systems and the computing resources have also been studied in this work as instruments of this management. To base adequately the theme of the dissertation, case studies were accomplished in two big construction and real estate development companies and in three building design offices. The case studies in the five companies made it possible to characterize the practices adopted for the design coordination, according to the alternatives used for its accomplishment (internal or external work or outsorced, besides the consultancy in coordination). A case study on knowledge management was also conducted in one of the major companies researched, aiming at studying its applicability in the building construction. The introduction of the concepts of knowledge management in the culture and in the organizational strategy of the company, as well as its reflex in the building design are presented. In agreement to this approach, by introducing the discussion about knowledge management, this work contributes to the process of development of designs and to its coordination, enabling the accomplishment of designs with better level of quality and constructability, to agree with the demands of the modern projects.
The coordination activities and the knowledge management in the building desing
Keywords: Projeto de engenharia; Projetos de edificações; Coordenação de projetos; Gestão do conhecimento; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL